The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13194874
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Persistent Organic Pollutants in Omental Adipose Tissue from Patients with Diffuse-Gastric Cancer: A Pilot Study

Abstract: The greater omentum represents a specific adipose tissue resected with gastric surgery for cancer. Diffuse gastric adenocarcinoma (diffuse-GC) is of major relevance among gastric cancers due to its unknown origin, aggressiveness, and metastasis in the peritoneal cavity. We postulated that persistent organic pollutants (POPs) could be detected in the greater omentum. Great omentum from patients with (i) diffuse-GC, or (ii) with other peritoneal metastatic cancer, and (iii) control group without cancer disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Whether or not the increase of CYP1s expression that we observed in diffuse as compared to intestinal GC is due to exposure to a specific or to multiple POPs remains to be established [64]. We have previously reported the significant and widespread increase of a substantial set of POPs such as polychlorinated dioxins (PCDDs/PCDFs), polychlorobiphenyls (PCBs) and polybrominated flame retardants (such as PBDE 209, a carcinogenic intermediate of BaP) in human omental tissue (fat deposits) from French patients with diffuse-GC, as compared to control biopsies [13]. Coexposure of TCDD and PBDE209 was observed in 33% of the omentum from patients with diffuse GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not the increase of CYP1s expression that we observed in diffuse as compared to intestinal GC is due to exposure to a specific or to multiple POPs remains to be established [64]. We have previously reported the significant and widespread increase of a substantial set of POPs such as polychlorinated dioxins (PCDDs/PCDFs), polychlorobiphenyls (PCBs) and polybrominated flame retardants (such as PBDE 209, a carcinogenic intermediate of BaP) in human omental tissue (fat deposits) from French patients with diffuse-GC, as compared to control biopsies [13]. Coexposure of TCDD and PBDE209 was observed in 33% of the omentum from patients with diffuse GC.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that polycyclic polyhalogenated hydrocarbons (like dioxins and PCBs) and polycyclic aromatic hydrocarbons (PAHs) including benzo[a]pyrene from tobacco-smoke and biomass burning) may link to relatively high health risk including cancers. We have previously shown that environmental chemicals such as persistent organic pollutants (POPs) are involved in breast cancers [12], and may accumulate in the Omentum adipose tissue of patients with GC [13]. In addition to TCDD, the prototypical and most potent known environmental ligand in animals and humans, other widespread environmental POPs contaminants bind aryl hydrocarbon receptor (AhR, a basic helix-loop-helix transcription factor) with strong affinities [14,15] and may chronically activate AhR in cancer agression.…”
Section: Introductionmentioning
confidence: 99%
“…Perrot‐Applanat et al. ( 2021 ) analysed BDE‐28 , ‐ 47 , ‐ 99 , ‐ 100 , ‐ 153 , ‐ 154 , ‐ 183 , ‐ 209 and a number of further POPs in greater omentum samples from 32 patients (16 men and 16 women). The pilot study included 14 patients with diffuse‐gastric cancer, 10 patients with other cancers (ovary or colon) that had metastasised in the peritoneal cavity and 8 patients operated for non‐cancer diseases serving as a control.…”
Section: Assessmentmentioning
confidence: 99%
“…The authors stated that the interpretation of the study was limited by a relatively large interindividual variation in the levels of the measured congeners, probably due to the heterogeneity in the study populations age and pretrial dietary habits. Perrot-Applanat et al (2021) analysed BDE-28, -47, -99, -100, -153, -154, -183, -209 and a number of further POPs in greater omentum samples from 32 patients (16 men and 16 women). The pilot study included 14 patients with diffusegastric cancer, 10 patients with other cancers (ovary or colon) that had metastasised in the peritoneal cavity and 8 patients operated for non-cancer diseases serving as a control.…”
Section: Other Human Tissuesmentioning
confidence: 99%
“…Human studies support the association of various OCPs (aldrin, dieldrin, endosulfan, HCH, DDT, 2,4,5-trichlorophenoxyacetic acid, phenoxy acid herbicides, and methoxychlor). The exposure (both occupational and non-occupational) has been strongly linked to increased incidence of non-Hodgkin’s lymphoma [ 22 ]; multiple myeloma [ 23 ]; soft tissue sarcomas [ 24 ]; lung cancers [ 25 ]; and cancers of the pancreas, stomach, liver, and kidney as well as urinary and gall bladder cancer [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Carcinogenic Effects Of Organochlorine Pesticidesmentioning
confidence: 99%